(untitled) (European Journal of Behavioral Sciences, 2020)
In the late 20th and 21st centuries, implementation of artistic research into the educational system has become increasingly intensive, both in the field of art as well as in the fields where arts collaborate with sciences. The subject of the paper is artistic research in the musical arts; how valuable is a piece of music created as a result of research from an artistic and scientific standpoint? The purpose of our study is to identify common and distinctive features of two different types of creative processes. To determine this, we use empirical and comparative research methods. To solve a scientific problem, we set a task - to compare the process of creating a piece with the process of artistic research, which results into a musical work. As artists describe their own creative process best of all, the paper is based on creative experience of Eka Chabashvili – the author of the current paper - as a composer. Two of her works are selected to describe the course and sequence of events that occurred in consciousness during their creation. The artistic process is divided into three main stages: 1) Source of inspiration and formation of the idea; 2) Transformation of the idea into musical notion and projection; 3) Materialization of the musical idea – its realization. Both compositions represent the combination of different components of artistic and technical ideas. Intuitive and rational tasks interchange with each other. The paper aims to determine the intuitive and rational ways of constructing musical concept.